Design of Large Underground Near Detector Cavern for Fermilab in Batavia, Illinois - RETC2021 - Irwan Halim; Seung Han Kim; David Mast (Society for Mining, Metallurgy & Exploration, 2021)
Fermilab is constructing a large underground cavern in Limestone to house scientific equipment. The cavern will have a complex L-shaped geometry and about 215-foot depth with relatively shallow rock cover, with service/egress shafts accesses into the cavern. Three-dimensional analytical models were developed to study the ground behavior and support performance. Multiple rock constitutive and failure models were evaluated. The models were significantly impacted by the high lateral in-situ earth pressure at the site. This paper will describe the design approaches that were taken to optimize the cavern arch geometry to allow safe construction in shallow rock, and permanent support requirements.